I'm not sure if I understand what you're asking, but here goes.

I think here:

You meant to say: (1+a1)(1+a2)

...as that would make a lot more sense.

n >=2, so let's start with the minimum case: n=2.

(1+a1)(1+a2) = 1 + a1 + a2 + a1a2

1+(a1+a2) = 1 + a1 + a2

The first expression > the second, because there's that extra a1a2 term in there.

This will be true for any n >= 2! This is because the expanded multiplication will always have all the terms of the simple addition, plus some additionals that are combinations of the a's.

That proof probably wouldn't satisfy a mathematician, but it sure works for me.